Relevance of Asian Philosophy to Philosophy of Education Today: An Interview with Roger Ames - Bai, Heesoon; Ames, Roger T. (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2010)
Professor Roger T. Ames is Professor in the Department of Philosophy at the University of Hawai‘i, Manoa. The following is a short excerpt from an interview with Professor Ames that took place on the eve of 2009 PESA Conference, December 1, 2009. Heesoon Bai, Editor of Paideusis, accompanied by Avraham Cohen, interviewed Professor Ames in his office.